Salt taste receptors and associated salty/salt taste-enhancing peptides: A comprehensive review of structure and function. (November 2022) - Le, Bei; Yu, Binbin; Amin, Mohammad Sadiq; Liu, Ruixi; Zhang, Na; Soladoye, Olugbenga P.; Aluko, Rotimi E.; Zhang, Yuhao; Fu, Yu
Abstract: Background: Long-term high sodium diet consumption has been largely implicated in the pathogenesis of several cardiovascular disease conditions. Non-sodium salts such as potassium chloride and calcium chloride are thus often used in the food industry to partially replace sodium chloride. But excessive use of these alternatives can negatively impact the sensory quality of foods. Therefore, the research, development and application of salty peptides and salt taste-enhancing peptides are promising as a potential salt reduction strategy. Scope and approach: This work firstly recapped the necessity of global salt reduction, followed by salt taste receptors and salt taste transduction mechanism. Subsequently, the recent progress on salty peptides and salt taste-enhancing peptides from different protein sources was reviewed. Furthermore, the main approaches used to evaluate salty peptides and salt taste-enhancing peptides were introduced. In addition, application prospects and the current challenges were discussed. Key findings and conclusions: The salty peptides and salt taste-enhancing peptides derived from food proteins are promising to be employed as an effective salt reduction strategy. This review can provide a theoretical reference for the food industry to reduce salt consumption by the use of salty peptides and salt taste-enhancing peptides. Graphical abstract: Image 1 Highlights: Salt taste-enhancing peptides can interact with human taste receptors. Maillard reacted peptides and γ-glutamyl peptides exhibit salt taste-enhancing effects. Salt taste-enhancing peptides can significantly enhance saltiness perception. Salt taste-enhancing peptides have a great potential for salt reduction in the food industry.